Penentuan Rute Jalur Distribusi Spasial Produk Air Mineral Aguamor (Studi Kasus: PT. Cherylindo Nusa Persada Kota Kupang) - Hiskia, Cheryl Louisa Loedwyca; Fibriani, Charitas (STMIK Banjarbaru, 2023)
The determination of spatial distribution routes for mineral water products is an important process in the mineral water business to ensure that products can be delivered to consumers efficiently and in a timely manner. In this process, factors such as distance, travel time, population density, and road infrastructure are considered to select the most effective and efficient routes. The determination of distribution route paths can be done using digital mapping technology and spatial analysis, which allows for the evaluation of various distribution routes. Spatial data such as road maps, population data, and consumer locations can be input into a Geographic Information System (GIS) to facilitate analysis and decision-making.There are several methods that can be used in determining distribution route paths, including heuristic methods, mathematical optimization, and genetic algorithms. Heuristic methods are usually used to select the nearest or fastest routes, while mathematical optimization and genetic algorithms are used to select the most efficient routes.In the determination of distribution route paths, there are several methods that can be used, including heuristic methods, mathematical optimization, and genetic algorithms. Heuristic methods are typically used to select the closest or fastest routes, while mathematical optimization and genetic algorithms are used to select the most efficient routes.Keywords: Geographic Information System; Route Mapping; Google Maps API; Mineral Water AbstrakPenentuan rute jalur distribusi spasial produk air mineral adalah suatu proses penting dalam bisnis air mineral untuk memastikan bahwa produk dapat dikirimkan ke konsumen dengan efisien dan tepat waktu. Dalam proses ini, faktor-faktor seperti jarak, waktu tempuh, kepadatan populasi, dan infrastruktur jalan dipertimbangkan untuk memilih rute yang paling efektif dan efisien. Penentuan rute jalur distribusi dapat dilakukan dengan menggunakan teknologi pemetaan digital dan analisis spasial yang memungkinkan pengevaluasian berbagai jalur distribusi yang berbeda. Data-data spasial seperti peta jalan, data populasi, dan lokasi konsumen dapat dimasukkan ke dalam Sistem Informasi Geografis (SIG) untuk memudahkan analisis dan pengambilan keputusan. Dalam penentuan rute jalur distribusi, terdapat beberapa metode yang dapat digunakan, antara lain metode heuristik, optimasi matematis, dan algoritma genetika. Metode heuristik biasanya digunakan untuk memilih rute yang paling dekat atau paling cepat, sedangkan metode optimasi matematis dan algoritma genetika digunakan untuk memilih rute yang paling efisien.Kata kunci: Sistem Informasi Geografis; Pemetaan Rute; Google maps API; Air Mineral.